A Comparative Analysis of Citation Counts in Sinta, Dimensions, and Scopus: A Study of Journals in Islamic Economics, Finance, and Business - Sudarsono, Heri; Ardiami, Kinanthi Putri; Anto, Mohammad Bekti Hendrie (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
This study compared the citation counts of journals in economics, finance, and Islamic business (JEFIB) indexed in three prominent databases: Sinta, Dimensions, and Scopus. JEFIB is indexed in Sinta, with citation data also available from the Dimensions and Scopus databases. A total of five journals were selected from each Sinta category, with the highest citation count from each database—Sinta, Dimensions, and Scopus—being recorded. The citation data were then tabulated for each journal group based on the highest counts from these three databases. The findings reveal that citation counts in Sinta do not always align with those in Dimensions and Scopus, primarily due to differences in the data sources used for citation tracking. Sinta relies on data from Google Scholar, encompassing a broader range of publications, while Dimensions tracks citations from journals indexed by Crossref. Scopus citations, on the other hand, depend on the total number of citations of journal articles included in the Scopus database. Furthermore, the citation counts are influenced by factors such as the number of journal volumes, the total number of published documents, and the accreditation level of the journal. This study underscores the importance of considering citation data from multiple platforms—Sinta, Dimensions, and Scopus—when evaluating the impact of journals within the global academic community.